HONEYCOMBING AND DEFORMATION OF SIX WOOD SPECIES AND THEIR RELATIONSHIP WITH SEVERAL PHYSICAL - Karnita Yuniarti; Efrida Basri; Abdurachman Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 2017)
It is presumed that the wood susceptibility to drying defects is related to several physical properties. This paper examines the drying defects: honeycombing and deformation of six wood species (trema, fast growing teak, bayur, jabon, angsana and lamtoro) during high temperature drying and analyses their relationship with initial moisture content, T/R shrinkage ratio and density. Terazawa method was used to examine the defect during high temperature drying. Result shows that after high temperature drying, lamtoro suffers the worst honeycombing (level 4-6), and fast growing teak deforms severely (level 4-6). Regression analysis shows multiple regression models using all physical properties as predictors provides better estimation on deformation and honeycombing than single-predictor regression models. The multiple regression model for each defect could explain 57.52% and 39.46% of variation in deformation and honeycombing, respectively.